Psychosocial and occupational functioning of women in menopause - Barnaś, Edyta; Krupińska, Aleksandra; Kraśnianin, Elżbieta; Raś, Renata (Menopause Review/Przegląd Menopauzalny, 2012)
Purpose : The purpose of this study was to evaluate psychosocial and occupational functioning of women in menopause through the analysis of the impact of selected socio-demographic factors on the course of menopause and their influence on women’s quality of life. Material and methods : A prospective study included 256 women in menopause aged between 48 and 58, residents of the Podkarpackie Voivodeship. The Kupperman Index, the Beck Depression Inventory (BDI), and the WHOQOL-BREF – a questionnaire assessing quality of life, were the research tools. The data were analysed using STATISTICA 8.0 software. Results: The study population was homogenous as far as the age was concerned. The average age of menopause was 51.5 years. The majority of respondents lived in the country with other members of their families (4 people on average). The biggest subgroup included married women. Professionally active respondents comprised 56.6% whereas 26.3% were unemployed, 11.2% retired and 5.9% were pensioners. According to the Kup- perman Index, the occurrence of menopause symptoms was determined by three variables: financial status (p = 0.019166), time since the last period (p = 0.030078), and occupational situation (p = 0.00324). No cases of severe depression (measured with BDI) were found among respondents. However, the most frequent findings were: no depressive symptoms or mild depression. The degree of depression correlated with the respondent’s financial status (p = 0.00964) and one’s sexual activity (p = 0.00324). Respondents’ quality of life was determined by their professional status (p = 0.0000) and whether hormonal therapy was taken (p = 0.008360). Conclusions : Menopause complaints, insufficient financial status, lack of hormonal therapy, and the lack of satisfaction with one’s sexual life determine poor psychosocial and occupational functioning, which decreases the quality of life of women in menopause.